The effect of equi-molar dietary betaine and choline addition on performance and carcass quality of pigs - Siljander-Rasi, Hilkka; Tiihonen, Kirsti; Peuranen, Seppo; Simmins, Howard (British Society Of Animal Science, 2001)
The results indicated that dietary betaine addition improved the performance of pigs restrictedly fed diets with diluted energy concentration as found by Cromwell et al. (1999). A maximal response to betaine addition was not observed in this trial. However, betaine did not affect carcass composition, unlike the results of Cromwell et al. (1999) which indicated a reduction of back fat with betaine addition. Choline addition had no effect on performance and carcass charateristics. On an equi-molar basis it appears that pigs respond to betaine rather than choline supplementation, although more work is needed to clarify the mode of action.
Keywords: Ko; betaiini; koliini; sika; ruokinta; rehut